Polymer Applications for Medical Care in the COVID-19 Pandemic Crisis: Will We Still Speak Ill of These Materials? - Corrêa, Harrison Lourenço; Corrêa, Daniela Gallon (Frontiers in Materials, 2020)
As consumption and use increased, the accumulation of urban waste of polymeric origin drew the attention of several sectors, especially that of the organized civil society. Through mobilizations and activism, environmental became more restricted regarding the use and disposal of polymer materials. Plastic bags, tires, disposable cups, plastic straws, PET bottles are some examples of how polymers have had a negative impact to the environment generating pressures around the world to rethink their uses. However, the pandemic crisis that emerged in January, 2020 has reinforced the importance of polymers for contemporary society. If, in the past, consumerism was the driving force behind the application of polymers, nowadays health and medical emergencies are the new forces. The reduction in stocks of medical-hospital supplies and personal protective equipment for health professionals and for the general public caused by the pandemic led to the emergence of alternative production movements based on polymers. Because of those alternatives, which have helped a lot to save and preserve lives, the present work aims to highlight the types of polymers most used during this pandemic period. For this purpose, scientific articles related to the production of masks and other devices having some type of polymer as raw material were analyzed. The present research was based on the first half of 2020, highlighting the countries, the polymer used, and the final product it is intended to.